Walking at the intersection of Seamon's place ballet and Relph's insideness: understanding how students experience the university as a place through their everyday habitual walking - Mtolo, Siyathokoza Monwabisi (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2020)
Walking as a way to experience a place is a relatively understudied area of phenomenological study. Furthermore, globally (the world) and locally (South Africa) the study of the experience of tertiary education institutions as walked environments is minimal (see Puig-Ribera et al., 2008; Speck et al., 2010; Mtolo, 2017). However, the events of the South African #MustFall moment "“ especially the #RhodesMustFall part of the moment and how it began with the desecration of a statue that was walked past and found to be a misplaced artefact in a society that is in postcolonial/post-Apartheid times and space "“ highlighted the pressing need to study the experience of the university as a place through which habitual walking takes the student through moments of movement, rest, and encounter that are a highly consequential way in which placeness is experienced. This study is a way to document how students at Rhodes University experience the university's placeness quality, through habitual walking, in an example of the way in which a place is experienced through moments of movement, rest, and encounter. For this study in-depth mobile interviews were conducted with 12 student participants from Rhodes University. The interviews were video-recorded as the participants talked while traversing through habitually walked areas of the campus that are the meaning-infused spaces which make up the Rhodes University that they traverse through on a daily basis. The dissertation found that in the experience of Rhodes University, through habitually walking its placeness, people experience moments of movement, rest, and encounter that are highly targeted and personalised. The experience of the Rhodes University campus is an experience of people and the built-up and decorated environment along similar lines. People bring to the experience of their walked space past experiences which inform consequentially how any space that is walked is experienced. People further employ strategies to ensure that the experience of walking a space is more to their desired quality as an experience, which ends up being meaningful and most likely to affect future instances of walking through meaning-infusing and meaning-infused space. Ultimately, the habitual walking of Rhodes University consequentially informs the relationship between students and Rhodes University's placeness, as the walking is a way of learning how to be within a placeness that is engaged through alternating moments of movement, rest, and encounter that incrementally 'open' for experience Rhodes University in such a targeted manner that every student eventually has their personal and customised Rhodes University by virtue of it being just those sites and situations which have been engaged through habitual walking.
Keywords: Seamon, David; Relph, EC; College students -- South Africa -- Makhanda -- Attitudes; Walking -- Sociological aspects; College students -- South Africa -- Makhanda -- Political activity; Rhodes University -- Students -- Attitudes; Student movements -- South Africa -- Makhanda